Electrical and Optical Investigations on Discotic Liquid Crystal Composite Systems - Supreet (My University, 2014)
Field of Discotic Liquid Crystal (DLC) research is more than 30 years old. The possibility to tune the properties of DLCs by simply preparing composites of liquid crystalline/nanomaterials or liquid crystalline/non liquid crystalline materials has opened up new horizons in the area of liquid crystal research. Our attempt is on understanding the science of DLC-composite systems based on their electrical and optical properties. Incorporation of nanomaterials in matrix of DLCs provides materials which possess unique properties of nanomaterials as well as self assembly, self healing and processing of DLCs. The work contained in this thesis deals with preparation and characterization of DLC composite systems and is divided into three parts. First part deals with characterization of pure and ZnO nanoparticles dispersed rufigallol based discotic liquid crystal. Second part deals with dispersion of gold nanoparticles in discotic liquid crystals comprise of triphenylene core. Third part deals with induction, variation, and stabilization of mesomorphic properties of disc-Like molecules composites based on charge transfer complex of disc-like molecule and TNF. Prepared composite systems were characterized using polarizing optical microscopy (POM), small-angle X-ray scattering (SAXS), differential scanning calorimetry (DSC), visible absorbance spectroscopy, dielectric spectroscopy, infrared (IR) dichroism technique, and electrical conductivity measurements As final conclusions, it may be affirmed that the thesis deals with the Electrical and Optical Investigations on Dispersed Discotic Liquid Crystal Composite Systems prepared by incorporation of nanomaterials in the supramolecular order of the columnar phase forming discotic liquid crystals. Following are the major findings of the thesis work: • Alignment and order parameter of DLC can be enhanced by dispersing ZnO nanoparticles in columnar matrix and by preparing charge transfer complexes of DLC with TNF. • Conductivity enhancement by order of two can be achieved by dispersing gold nanoparticles in the columnar matrix. • Transition temperatures variation, variation, stabilization and induction of mesophases can be achieved by forming charge transfer complexes of DLC with TNF. We have shown that properties of pure DLCs can be tuned, enhanced, varied according to their application in opto-electronic devices by preparing different dispersed DLC composite systems. These inorganic-organic liquid crystal hybrid systems may be extremely important for many device applications such as photovoltaic solar cell, photoconduction, light emitting diodes, thin film transistors etc.
PHD, SPMS
Keywords: Columnar phase; disc like liquid crystal composites systems; orientational order parameter; dielectric properties; optical properties